Diversity of Lichens along Elevational Gradients in Forest Ranges of Chamarajanagar District, Karnataka State - Rashmi, S.; Rajkumar, H.G. (International Journal of Scientific Research in Biological Sciences, 2019)
The lichen species richness in Chamarajanagar district in Karnataka, India were assessed using altitudinal gradient, in order to compare distribution patterns of different growth forms, dominant families and diversity index. Four major forest ranges, Biligiriranga Hills, Himavad Gopalaswamy Hills, Malay Mahadeshwara Hills, and Shivanasamudra Falls were surveyed and a total of 97 lichens, belonging to 47 genera and 25 families were recorded. Physciaceae was found to be dominant family by 18 species under 8 genera, followed by Parmeliaceae with 16 species under 4 genera. Crustose type was dominated with 51%, followed by foliose type with 38%. Malay Mahadeshwara hills had highest lichen species richness and harboured 67 species, of which, 36 species were crustose type and 28 species were foliose type. Shannon-weiner index ranged from 3.85- 2.45 and Simpson index of diversity ranged from 0.02-0.09. Luxuriant growth of lichens was recorded at the altitude of mid elevation with degree of abundance, density, frequency and distribution of the lichen species compared to other elevation. The present study provided baseline data of lichen diversity, which helps in understanding the relationship between distribution of lichen species along different elevation bands and vegetation types.